Productive Development Pole for Tulcan - Silva Delgado, Jorge Patricio (2022)
This study has analyzed the territorial planning for canton Tulcan, as well as its process of harmonic development at the geophysical, social, economic, ecological and institutional-political levels. The combination of these elements and variables are then analyzed and parameterized in order to qualitatively evaluate their corresponding correlations and incidences. Afterwards, particular problems are found, as well as any strengths and opportunities in the territory with an action strategy that promotes sustainable development. In order to achieve this, a mixed method was used including both quantitative and qualitative elements, and considering categories with economic factors and mechanisms and instruments to develop competitive advantages that promote local earnings. With this analysis, the Development Pole is proposed as an alternative instrument that allows canton Tulcan to overcome its standstill at the economic and social levels.